The application of the Unified Theory of Acceptance and Use of - Fakhrun Shiddieq, Diqy (RISTEC : Research in Information Systems and Technology, 2023)
The application of information and communication technology is often not achieved due to the unwillingness of users to accept and use the existing system. The purpose of this study wa s to analyze the relationship between the determinant factors of SIMAK utilization on the user's behaviora l intention, to ana lyze the rela tionship between habit and facilitating condition factors to user behavior, and to ana lyze the relationship between user behavior intention and user behavior. This study used a quantitative method by conducting a questionnaire survey to Digital Business Study Program student, Ga rut University. Measurements were carried out using the UTAUT 2 model construct, then testing wa s carried out with the Structura l Equation Model (SEM) and SPSS. This finding proves that 1) performance expectancy, effort expectancy, socia l influence, facilitating condition, and hedonic motivation have no effect on behaviora l intention. 2) habit and trust in information have an effect on behaviora l intention. 3) habit and facilitating conditions have no effect on user behavior. 4) behaviora l intention has an effect on user behavior. The implications of this resea rch can be considered in the application of information and communication technology in improving performance.